Distribution and composition of redox-active species and dissolved organic carbon in Arctic lacustrine porewaters - Danhui Xin; Jeffrey M. Hudson; Anthony Sigman-Lowery; Yu-Ping Chin (Arctic, Antarctic, and Alpine Research)
The interaction between redox-active species and dissolved organic carbon (DOC) is crucial in driving lacustrine benthic microbial processes. In lacustrine porewaters, many redox-active species exist in their reduced form, while DOC acts as a substrate and an electron acceptor. Understanding the types and abundance of redox-active species in porewaters along with their complementary DOC substrate is pivotal for gaining insights into benthic processes, particularly in regions susceptible to climate change. We report the in-situ measurement of redox-active species in sediment porewaters, alongside the ex-situ measurement of DOC extracted from cores collected from two Arctic lakes (Toolik and Fog 1). Fe2+ was abundantly detected below 4 cm of the sediment-water interface in all cores and was inversely related to dissolved O2. Additionally, two distinct Fe(III)-complexes were identified. DOC ranged in the order of 10s of mg/L and either remained stable or increased with depth. A comparison between Toolik and Fog 1 lakes revealed a higher accumulation of Fe2+ and DOC in the latter. This study marks the first of its kind to assess spatial distributions of redox-active species and DOC as a function of depth from multiple sites in Arctic lacustrine porewaters.